AN APPROACH TOWARD SUSTAINABILITY ON CROSS BORDER REGIONS - Avendaño-Leadem, Daniel Francisco (Revista Geográfica de América Central., 2013)
Due to the peripheral conditions of most cross-border regions (CBR) around the world, managing and protecting environmental resources together with the improvement of socioeconomic conditions have posed a constant challenge. The aim of this paper is to identify the most important elements to consider on the path toward promoting the sustainable development of CBRs. It begins with an overview of development experiences of these types of regions in Europe, North America and Asia. It continues by differentiating conventional regional development from the CBR approach in order to establish the core aspects of applying sustainability within these spaces. The article concludes by proposing an evaluation method to facilitate the assessment of sustainability planning on CBRs and contribute to further development of the topic.